2019
DOI: 10.3390/su11164300
|View full text |Cite
|
Sign up to set email alerts
|

Soil Organic Carbon Accumulation in Post-Agricultural Soils under the Influence Birch Stands

Abstract: The aim of this study was to demonstrate the effects birch renewal on the soil organic carbon accumulation and on dehydrogenase activity. We selected 12 research plots with birch stands of different ages (1-4 years, 5-8 years, 9-12 years, and 13-17 years) to determine soil texture, pH, total carbon and nitrogen levels, and base cation content. The total organic carbon stock was calculated for the soil profiles. Additionally, dehydrogenase activity was determined. Naturally regenerated birch stands on post-agri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…The field sites were located in an area dominated by Podzols, Luvisols and Cambisols [52]. Soils dominant in the study area were formed from similar geological substrates (glacial sand) and characterised by a similar texture (loamy sand) [53]. Depth of the former ploughing horizons was 30 cm.…”
Section: Study Sitesmentioning
confidence: 99%
“…The field sites were located in an area dominated by Podzols, Luvisols and Cambisols [52]. Soils dominant in the study area were formed from similar geological substrates (glacial sand) and characterised by a similar texture (loamy sand) [53]. Depth of the former ploughing horizons was 30 cm.…”
Section: Study Sitesmentioning
confidence: 99%
“…However, a simultaneous interaction of mycorrhizal fungi in the roots of fir stands should be considered. Similarly, Gawęda et al [24] confirmed the beneficial effect of birch stand regeneration on the dehydrogenase activity of post-agricultural land.…”
Section: Introductionmentioning
confidence: 80%
“…Therefore our expectations considering the rapid increase of SOC after the afforestation of post‐agricultural lands was confirmed. Additionally, Cukor et al (2017) and Gawęda et al (2019) proved that the increase in SOC stock and a decrease in soil pH on post‐agricultural land is related to increasing stand age. We have recorded that Mn content had the highest value in oak stands growing on post‐agricultural land.…”
Section: Discussionmentioning
confidence: 99%